Fungal diagnostics : methods and protocols - Glynn, Barry; O'Connor, Louise (Methods in Molecular Biology, 2013)
This Methods in Molecular Biology(t) book focuses specifically on fungal detection in clinical settings, including fungal diagnostics, environmental testing, agriculture and food production and veterinary diagnostics. Offers materials lists, tips and protocols